Subunit composition of a bicomponent toxin: Staphylococcal leukocidin forms an octameric transmembrane pore - Miles, George (Cold Spring Harbor Laboratory Press, 2002)
Staphylococcal leukocidin pores are formed by the obligatory interaction of two distinct polypeptides, one of class F and one of class S, making them unique in the family of β-barrel pore-forming toxins (β-PFTs). By contrast, other β-PFTs form homo-oligomeric pores; for example, the staphylococcal α-hemolysin (αHL) pore is a homoheptamer. Here, we deduce the subunit composition of a leukocidin pore by two independent methods: gel shift electrophoresis and site-specific chemical modification during single-channel recording. Four LukF and four LukS subunits coassemble to form an octamer. This result in part explains properties of the leukocidin pore, such as its high conductance compared to the αHL pore. It is also pertinent to the mechanism of assembly of β-PFT pores and suggests new possibilities for engineering these proteins.